Динаміка товщини стінок шлуночків та міжшлуночкової перегородки серця щурів в ранньому післянатальному періоді в нормі та після внутрішньоплідного впливу дексаметазону - Григор'єва, Олена Анатоліївна; Чернявський, Артур Валерійович; Григорьева, Е. А.; Чернявский, А. В.; Hryhorieva, O. A.; Cherniavskyi, A. V. (Чорноморський національний університет ім. Петра Могили, 2018)
Мета дослідження – вивчити динаміку товщини стінок шлуночків та міжшлуночкової перегородки серця щурів в ранньому післянатальному періоді в нормі та після внутрішньоплідного впливу дексаметазону. В роботі використані морфометричні та статистичні методи. Встановлено, що після внутрішньоплідного введення дексаметазону у новонароджених щурів спостерігається потовщення стінок правого та лівого шлуночків та міжшлуночкової перегородки у порівнянні з контрольною групою, тенденція до збільшення протягом першого тижня, та їх стоншення до кінця першого місяця, що може бути обумовлено зниженням проліферативної активності кардіоміоцитів і, як наслідок - зменшенням їхньої популяції. Резюме. Цель исследования – изучить динамику толщины стенок желудочков и межжелудочковой перегородки сердца крыс в раннем постнатальном периоде в норме и после внутриплодного воздействия дексаметазона. В работе использованы морфометрические и статистические методы. Установлено, что после внутриплодного введения дексаметазона у новорожденных крыс наблюдается утолщение стенок правого и левого желудочков и межжелудочковой перегородки по сравнению с контрольной группой, тенденция к увеличению в течение первой недели, и их истончение к концу первого месяца, что может быть обусловлено снижением пролиферативной активности кардиомиоцитов и, как следствие – уменьшением их популяции. Abstract. A significant part of cardiovascular system diseases in children is occupied by conditions and functional disorders associated with dysplasia of the heart connective tissue, which is caused by a number of factors, one of which is the adverse effect of various factors on the fetus in the antenatal period of development. The synthesized glucocorticosteroid dexamethasone is administered to pregnant women in the third trimester from risk of preterm delivery, to improve the surfactant system maturation in the fetus, to reduce the incidence of respiratory distress syndrome in newborns. The safety of using synthetic glucocorticoids in pregnant women is the subject of active discussions due to possible adverse effects of dexamethasone on the development of the fetus and, in particular, on the heart of the future child. The purpose of this research is to study the dynamics of the ventricles walls thickness and interventricular septum of the rats’ heart in the early postnatal period in normal conditions and after intranatal injection of dexamethasone. Materials and methods. Three groups of rats were examined in the research: the first one included intact animals; the second was comprised of experimental animals, who were injected by dexametazone by intrauterine, transcutaneous approach after conducting a median laparotomy of pregnant rat at the 17th day of pregnancy; the third group was formed by control animals, who were injected by saline solution in equal volume, by the same way, at the same day. Rats’ hearts were analyzed from birth up to the 45th day of life. Morphometric and statistic methods have been used during the research. Results and discussion. It was defined that after intrauterine fetal exposure of dexamethasone in newborns and on the 5th day after birth thickness of the right ventricle wall was significantly higher than in saline control group, due to possible premature cardiomyocytes maturation. This tendency lasted for the first two weeks, after that the differences equalized, and at the 45th day of experiment it became even thinner than in control group. This fact may be caused by decreasing of the cardiomyocytes’ proliferative activity and, as a consequence, by decreasing of their population. The thickness of the left ventricular wall was significantly higher during the first and the third day in experimental animals in comparison with those injected with the saline, and from the 5th day it became smaller. This tendency continued until the 45th day after birth, when these differences equalized. A similar situation was observed in the dynamics of the thickness of the interventricular septum: in newborn animals and on the 3rd day after birth, the septum was thicker in the experimental group compared with the control, where it decreased until the 45th day. Conclusions. The intrauterine fetal administration of dexamethasone leads to thickening of the right and left ventricles walls and interventricular septum in newborn rats. The tendency to increase during the first week and their thinning by the end of the first month was observed. This may be caused by the decreasing of the proliferative activity of cardiomyocytes and consequential decreasing of their population.
Динамика толщины стенок желудочков и межжелудочковой перегородки сердца крыс в раннем постнатальном периоде в норме и после внутриплодного воздействия дексаметазона
Dynamics of ventricular wall and interventricular septum thickness of rat’s heart in the early postnatal period in normal conditions and after intranatal injection of dexamethasone
Keywords: морфогенез; серце; внутрішньоплідний вплив; глюкокортикоїд; сердце; внутриплодное воздействие; глюкокортикоид; morphogenesis; heart; intrauterine fetal exposure; dexamethasone